Evaluation of the Effectiveness of Maggot Compost and Chicken Manure Fertilizer on Sunflowers in Sandy Land - Obel Obel; Warnita Warnita; Benni Satria; Aprizal Zainal; Armansyah Armansyah; Muhammad Agil Mustafa; Muhammad Fiqri (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2026)
Sunflowers have excellent prospects for future development in Indonesia. This commodity offers a variety of uses, from food and medicine to industrial use and even as a beauty product. Currently, development is focused on marginal land, particularly sandy soil. However, such land is known to have various limitations, necessitating innovations to enable its use as cultivation. One such approach is the application of fertilization technology using maggot compost and chicken manure. The purpose of this study was to evaluate the effectiveness of maggot compost and chicken manure on sunflowers in sandy soil. This study was conducted in Pasir Putih, Padang City, from June to September 2025. The design used in this study was a randomized block design with two factors and three replications. The first factor was the dose of maggot compost and the second was the dose of chicken manure. The results showed that the application of chicken manure and maggot compost at various doses resulted in increased growth and yield of sunflowers in sandy soil with each dose increase. Maggot compost at a dose of 20 g/plant and chicken manure at a dose of 30 g/plant had an interaction on plant height. Meanwhile, at a dose of 20 g/plant of chicken manure fertilizer and 15 g/plant of maggot compost, there was an interaction on the number of sunflower seeds.